Adjuvant therapeutic approaches of HER2-positive breast cancer with a focus on neratinib maleate. Issue 6 (3rd June 2019) - Kotecki, N.; Gombos, A.; Awada, A.
ABSTRACT: Introduction : Breast cancer (BC) is the most common cancer in women. Human epidermal growth factor receptor 2-positive (HER2-positive) BC represents up to 15% of all BC cases and is associated with a poor prognosis. Despite the substantial improvement obtained with the addition to the treatment of trastuzumab in this subtype of BC, disease recurrence can still occur. Areas covered : Anti-HER2 targeting drugs such as trastuzumab, pertuzumab, and T-DM1 have shown significant results in (neo)adjuvant setting. In this article, we will focus on available data for neratinib to reduce BC recurrence based mainly on the results of the ExteNET trial. This trial aimed to investigate whether neratinib can further reduce the risk of recurrence of patients diagnosed with HER2-positive BC. This trial demonstrated a significant reduction in the risk of invasive disease-free survival, particularly in hormone receptor-positive population. In addition, this review provides an expert opinion and analysis of the current situation in the adjuvant HER2-positive BC setting and in particular the escalation strategy of HER2 targeting. Expert opinion : The treatment landscape of HER2 positive BC in this setting will evolve in the coming years with a need for clinical and molecular perspective tools to guide therapy.